Properties of Sr- and Sb-doped PZT-Portland cement composites - A. Chaipanich (2018)
Lead zirconate titanate (PZT) ceramic-cement-based composites have increasingly been recognized as an attractive new composite material for use as a sensor in structural applications. In this work, PZT was doped with Sr and Sb (PSZT) to give it greater dielectric constant (ε r) and higher piezoelectric coefficient (d 33) values than normal PZT and is the first time that it is mixed with normal Portland cement to produce a 0-3 connectivity PSZT-Portland cement composite using PSZT contents of 50% and 70% by volume. Scanning electron micrographs show PSZT ceramic particles closely surrounded by the hydrated cement matrix where a dense microstructure can be observed in the interfacial zone. Both the ε r and d 33 values were found to increase with PSZT content and the values are amongst the highest so far for these types of composites, where the ε r and d 33 values reached 590 and 48 pC/N, respectively. © 2008 Springer-Verlag.